Implementasi Akad Ju’alah Dalam Lembaga Keuangan Syariah - Afriani Afriani (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2018)
Jualah is a kind of a promise expressed by someone who lost something of his lost item by giving some kind of reward to the one who found it, with certain limitations. Things are usually done for things that are considered very important. Ju'alah concept that most people understand almost the same as the concept of ijarah so that in understanding an act mu'amalah sometimes different understand. Well for more details what is meant by ju'alah? Jualah or jialah, derived from Arabic: ja'ala-yaj'alu-ja'lan. Ja'ala is literally meaningful to make or make, while Ju'alah means wage, price or salary. Everyday life we often encounter someone who lost his son, because the child is very very important for his parents so that the lost parents are holding a contest, who can find it will be given a gift with the conditions set by. In this case the author. Will try to discuss the justification agreement meaning etymology means wages or rewards given to someone because the person is doing or performing a particular job. The terminology of fiqih means